Reliability modeling and analysis for deadline-constrained grid service - Mahato D.P.; Singh R.S. (My University, 2025)
Reliability modeling and analysis of deadline-constrained grid computing system is a complex task. Additionally, a task must be completed within its given deadline. Therefore, deadline-miss failure is another type of failure which must be explained. This paper presents hierarchical model and analysis for the deadline-constrained grid service reliability. © 2018 IEEE.